(untitled) (Biological Sciences - PJSIR, 2007)
Study of co-combu st i on of d i esel oi l an d prod u cer gas from a gasi fier , i n d i v i d uall y as we ll as combi n ed , i n an ex pe r i mental com bu sti on ch am ber revea l ed t h at t h e prod u cer gas can be co-com bu sted w i t h l iq u i d fuel. The process p rod u ced m ore CO, NO" S01 and CO2 as com pared to t h e com bu st i on of d i ese l oi l a l one; th e ex h au st tem pe r a tu re for t h e process w a s h i gh e r th an t h t: d i esel com bu sti on a l on e .